Associação entre carga de treinamento, qualidade de sono e lesões musculoesqueléticas em atletas com lesão medular - Mario Antonio de Moura Simim (2017)
The objective of this thesis is to investigate the relationship between sleep quality, training load and risk of musculoskeletal injuries in wheelchair Rugby athletes with spinal cord injury (SCI). Seven male wheelchair rugby athletes with SCI participated in the study. Training load data were collected over four weeks, with recording of actigraphy data within 10 days. To quantify the training load, the Edwards TRIMP method was used. The Pittsburgh Sleep Quality Index was used to subjectively assess quality and sleep habits. The recording of musculoskeletal injuries by means of a retrospective questionnaire. The acute:chronic workload ratio (ACWR) was used to correlate training load and the risk of musculoskeletal injuries. Descriptive statistics were used to summarize the results, while repeated measures ANOVA, independent t test and linear regression model were used to compare and verify associations between variables. Our results indicated that the high wake after sleep onset WASO (33.7 ± 35.7 minutes) is a predictor for musculoskeletal injuries in athletes with SCI (R2 = 0.899). We also noticed an increase in ACWR indicating a higher propensity to musculoskeletal injuries (ACWR > 1.0). We conclude that athletes with SCI present poor sleep quality, exhibit high WASO, being this predictor for musculoskeletal injuries.